HUBUNGAN PENERAPAN PEMBELAJARAN EDUTAINMENT TERHADAP PENINGKATAN MUTU PENDIDIKAN INKLUSI DI SEKOLAH KREATIF SD MUHAMMADIYAH 16 SURABAYA - Sati; Azizah, Ratna Nur; Sita Diniasih; Nunung Sunari; Eriska Aufha Nurani; Jamilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Inclusive education at the Creative School of Muhammadiyah 16 Elementary School, Surabaya aims to provide equal learning opportunities for all students, including students with special needs. Therefore, it is necessary to implement edutainment learning that combines education and entertainment, so that it can improve the quality of inclusive education at the school. This study aims to determine the relationship between the implementation of edutainment learning and improving the quality of inclusive education at the Creative School of Muhammadiyah 16 Elementary School, Surabaya. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The subjects of this study include teachers, students, parents, and principals. The results of the study indicate that the implementation of edutainment learning can improve student motivation, understanding, and involvement. Teachers apply educational games, videos, and projects to adjust the material to students' needs. The implementation of this learning also helps students with special needs adapt and improve social skills. Challenges faced in implementing this learning include limited facilities and teacher readiness. To overcome this, the school held teacher training and collaborated with the education community. In conclusion, the implementation of edutainment learning is effective in improving the quality of inclusive education. With further support, this learning can be implemented in more schools.Keywords: edutainment, inclusive education, interactive learning.